The Impact of Inventory Management Innovations on Industry 4.0 Manufacturing Strategies - Nagy, Gábor; Szentesi, Szabolcs (Tehnički glasnik, 2025)
In general, the goal of inventory management mechanisms is to develop inventory ordering rules that ensure optimal inventory levels. By "optimal inventory level," we mean a level where stock is always available when needed, while storage costs are minimized. To achieve this, a thorough understanding of inventory-related costs is essential for determining the economical level. In addition to classical and widely used inventory management mechanisms, many companies also employ mixed or hybrid inventory strategies, which are based on the combination of elements from different systems. In Industry 4.0 manufacturing, determining the inventory levels of raw materials and semi finished products presents a significant challenge for logistics professionals. Developments in Logistics 4.0, as well as advanced hybrid inventory management mechanisms, can provide substantial support to professionals in optimizing inventory levels.